Mapping Global Research on Examination Accommodations for Students with Disabilities: A Bibliometric Study - Nurul Sallyna Rostam; Syar Mezee Mohd Rashid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study presents a bibliometric analysis of research trends on test accommodations for students with disabilities, aiming to clarify publication patterns and thematic development in this field. Examination accommodations are essential for ensuring fairness, accessibility, and equity in assessment practices within special and inclusive education contexts. Bibliographic data were retrieved from peer-reviewed journal articles indexed in the Scopus database within a defined time frame. Descriptive bibliometric indicators were used to examine annual publication trends, leading journals, prolific authors, contributing countries, and collaboration networks. In addition, keyword co-occurrence analysis was conducted to identify dominant research themes. The findings reveal a steady increase in scholarly output, indicating growing global attention to inclusive examination practices and equitable assessment policies. Key themes include test fairness and validity, policy and legal frameworks, types of accommodations, and challenges in implementation. Overall, this bibliometric analysis provides an overview of the evolution of research on test accommodations for students with disabilities and offers insights to guide future research and practice in special and inclusive education.